2018
DOI: 10.1038/d41586-018-06629-1
|View full text |Cite
|
Sign up to set email alerts
|

Calling time on New Zealand’s oldest tree species

Abstract: Tighten attribution of weather events Your claim that the connection between extreme weather and climate change is "now routine and reliable science" misrepresents the current state of climate-extreme attribution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…According to the ITRDB database, there were 197,855 cored old trees, 620 trees (0.31%) ≥1000 years, 18 trees (0.009%) ≥2000 years, and 1 tree >3000 years old. Therefore, unlike the frequently reported extremely old trees ≥2000 years in many countries (e.g., Black et al, 2018;Liu et al, 2019a), we found that local estimates of tree ages for extremely old trees based on tree diameters or tree height are probably inaccurate. For example, at least 102 counties in China, many of which are in the eastern parts of the country with high population densities, claim to have living trees >1000 years old (Liu et al, 2019a).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…According to the ITRDB database, there were 197,855 cored old trees, 620 trees (0.31%) ≥1000 years, 18 trees (0.009%) ≥2000 years, and 1 tree >3000 years old. Therefore, unlike the frequently reported extremely old trees ≥2000 years in many countries (e.g., Black et al, 2018;Liu et al, 2019a), we found that local estimates of tree ages for extremely old trees based on tree diameters or tree height are probably inaccurate. For example, at least 102 counties in China, many of which are in the eastern parts of the country with high population densities, claim to have living trees >1000 years old (Liu et al, 2019a).…”
Section: Discussioncontrasting
confidence: 94%
“…However, there can be long‐lived trees at low elevations in human‐dominated landscapes, such as in ancient temples and cities and along rivers (Liu et al., 2019a; Stahle et al., 2019). Indeed, people in many regions (including those in densely populated areas) worship old trees and protect these trees (Black et al., 2018; Blicharska & Mikusiński, 2014). However, such trees are often not scientifically dated and were rarely included in our database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. agathidicida infects kauri of all ages via the roots, causing trunk lesions, canopy thinning, root and collar rot, and ultimately death (Bellgard et al 2016). While kauri dieback disease was first documented in the 1970s, it has spread rapidly in the past decade and now poses a significant long-term threat to the species (Black et al 2018; Waipara et al 2013).…”
Section: Introductionmentioning
confidence: 99%